Spin and Orbital Magnetisms of NiFe Compound: Density Functional Theory Study and Monte Carlo Simulation. (March 2018) - Masrour, R.; Jabar, A.; Hlil, E. K.; Hamedoun, M.; Benyoussef, A.; Hourmatallah, A.; Bouslykhane, K.; Rezzouk, A.; Benzakour, N.
Abstract : The self-consistent ab initio calculations based on the density functional theory approach using the full potential linear augmented plane wave method are performed to investigate both the electronic and magnetic properties of the NiFe compound. Polarized spin within the framework of the ferromagnetic state between magnetic ions is considered. Also, magnetic moments considered to lie along (001) axes are computed. The Monte Carlo simulation is used to study the magnetic properties of NiFe. The transition temperature T C, hysteresis loop, coercive field and remanent magnetization of the NiFe compound are obtained using the Monte Carlo simulation .